Understanding Physics - Cummings, Karen (Wiley, 2004)
Keywords: Physics; dept.phy; faculty_collection

Understanding Physics: Students Solutions Manual - Cummings, Karen (Wiley, 2004)
Keywords: Physics; Physics; Problems, exercises, etc; dept.phy; faculty_collection

Theory of paramagnetic scattering in highly frustrated magnets with long-range dipole-dipole interactions: The case of the Tb2Ti 2O7 pyrochlore antiferromagnet - Enjalran, M.; Gingras, M.J.P. (Physical Review B - Condensed Matter and Materials Physics, 2004)
Highly frustrated antiferromagnets composed of magnetic rare-earth moments are currently attracting much experimental and theoretical interest. Rare-earth ions generally have small exchange interactions and large magnetic moments. This makes it necessary to understand in detail the role of long-range magnetic dipole-dipole interactions in these systems, in particular, in the context of spin-spin correlations that develop in the paramagnetic phase, but are often unable to condense into a conventional long-range magnetic-ordered phase. This scenario is most dramatically emphasized in the frustrated pyrochlore antiferromagnet material Tb2Ti2O7, which does not order down to 50 mK despite an antiferromagnetic Curie-Weiss temperature TCW∼-20 K. In this paper we report results from mean-field theory calculations of the paramagnetic elastic neutron scattering in highly frustrated magnetic systems with long-range dipole-dipole interactions, focusing on the Tb2Ti2O7 system. Modeling Tb 2Ti2O7 as an antiferromagnetic 〈111〉 Ising pyrochlore, we find that the mean-field paramagnetic scattering is inconsistent with the experimentally observed results. Through simple symmetry arguments we demonstrate that the observed paramagnetic correlations in Tb 2Ti2O7 are precluded from being generated by any spin Hamiltonian that considers only Ising spins, but are qualitatively consistent with Heisenberg-like moments. Explicit calculations of the paramagnetic scattering pattern for both 〈111〉 Ising and Heisenberg models, which include finite single-ion anisotropy, support these claims. We offer suggestions for reconciling the need to restore spin isotropy with the Ising-like structure suggested by the single-ion properties of Tb3+.
Keywords: anisotropy; antiferromagnets; article; atom; calculation; dept.phy; dipole; magnetism; mathematical analysis; molecular interaction; neutron scattering; oxygen; paramagnetic scattering; temperature; terbium; thallium; theory

Neutron scattering investigation of the spin ice state in Dy 2Ti2O7 - Fennell, T.; Petrenko, O.A.; Fåk, B.; Bramwell, S.T.; Enjalran, M.; Yavors'kii, T.; Gingras, M.J.P.; Melko, R.G.; Balakrishnan, G. (Physical Review B - Condensed Matter and Materials Physics, 2004)
Dy2Ti2O7 has been advanced as an ideal spin ice material. We present a neutron scattering investigation of a single-crystal sample of 162Dy2Ti2O 7. The scattering intensity has been mapped in zero applied field in the h,h,l and h,k,0 planes of reciprocal space at temperatures between 0.05 and 20 K. The measured diffuse scattering has been compared with that predicted by the dipolar spin ice model. The comparison is good, except at the Brillouin-zone boundaries where extra scattering appears in the experimental data. It is concluded that the dipolar spin ice model provides a successful basis for understanding Dy2Ti2O7, but that there are issues which remain to be clarified.
Keywords: Monte Carlo method; article; crystal; dept.phy; dysprosium; neutron scattering; temperature; temperature dependence; titanium

A hybrid epitaxy method for InAs on GaP - Chen, A; Yulius, Aristo; Woodall, J M; Broadbridge, Christine (Applied Physics Letters, 2004)
The interface formation mechanism during the molecular-beam epitaxy (MBE) of InAs/GaP has been studied with the aid of the In-Ga-P phase diagram. It is discovered that an initial dissolution and crystallization process similar to liquid phase epitaxy (LPE) may happen at sufficiently high temperature, resulting in a graded composition at the interface. Consequently, "parasitic LPE/MBE" is the name for this hybrid form of MBE. High-resolution TEM images confirm the existence of the interfacial layer in the sample grown at high temperature. The graded interface smears out the band offset and leads to a nonrectifying heterojunction. Low-temperature (LT) MBE growth can turn off the LPE component, enabling the growth of an abrupt interface. Based on this "LPE/MBE" model, a LT MBE technique is developed to grow an abrupt InAs/InGaP interface for heterojunction power Schottky rectifiers. The LT InAs/InGaP heterojunction demonstrates nearly ideal Schottky rectifier characteristics, while the sample grown at high temperature shows resistive ohmic characteristics. The LT InAs/InGaP Schottky diode also demonstrates good stability with respect to anneal temperature, similar to the InAs/GaP heterojunctions. © 2004 American Institute of Physics.
Keywords: Baliga figure of merit (BFOM); Current voltage characteristics; Liquid phase epitaxy; Metal-semiconductor (MS) diodes; Molecular beam epitaxy; Phase diagrams; Rapid thermal annealer (RTA); Rapid thermal annealing; Schottkey rectifiers; Schottky barrier diodes; Semiconducting gallium compounds; Semiconducting indium compounds; Transmission electron microscopy; dept.phy

Attitudes Toward Problem Solving as Predictors of Student Success - Cummings, Karen (2003 PHYSICS EDUCATION RESEARCH CONFERENCE: 2003 Physics Education Conference, 2004)
Keywords: dept.phy

Vapor-liquid-solid growth of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition - Su, J; Gherasimova, M; Cui, G; Han, J; Lim, Sangyun; Ciuparu, Dragos; Pfefferle, Lisa D; He, Y; Nurmikko, A V; Broadbridge, Christine; Lehman, Ann Hein; Onuma, T; et al. (2004)
We report flexible synthesis of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition (MOCVD) via a catalytic vapor-liquid-solid (VLS) growth mechanism. Indium is used as an in-situ catalyst to facilitate and sustain the stability of liquid phase droplet for VLS growth based on thermodynamic consideration. The employment of mesoporous molecular sieves (MCM-41) helps to prevent the coalescence of catalyst droplets and to promote nucleation statistics. Cathodoluminescence (CL) of GaN nanowires shows near band-edge emission at 370nm, and strong E 2 phonon peak is observed at room temperature in Raman scattering spectra. Both binary GaN and AlN nanowires have been synthesized by MOCVD. Three-dimensional AlN/GaN trunk-branch nanostructures are reported to illustrate the versatility of incorporating the VLS mechanism into MOCVD process. © 2005 Materials Research Society.
Keywords: Catalysis; Heterojunctions; Metallorganic chemical vapor deposition; Molecular beam epitaxy; Nanoelectronics; Nanostructured materials; Nanowires; Nucleation; Optical characterization; Synthesis (chemical); Thermodynamics; Vapor-liquid-solid (VLS) growth; dept.phy